Framing, Following, Middling: Towards Methodologies of Relational Materialities - Milla Tiainen; Katve-Kaisa Kontturi; Ilona Hongisto (Melbourne University Press/UTSePress, 2022)
Through the conceptual triptych of framing, following and middling, this article explores the composition and importance of materialities beyond their seemingly stable and measurable objectivity. Drawing on recent insights about concepts as generative of practice and as a practice in their own right, the article offers this triptych as potential new materialist ‘methodological metamodellings’ that acknowledge and render palpable the plural forces of formation in a research process. The article demonstrates this with the vibrant and relational materialities of Björk’s Biophilia Live (2014). This concert film intersperses the scientific with the affective, audiovisual performance with myriad forms of nature’s mediatised liveness, and the human with more-than-human scales of existence.